Effectiveness Of Use Of Historical Educational Games On Student Learning Outcomes - Najuah, N; Sidiq, Ricu; Suhendro Lukitoyo, Pristi (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
Learning media has a significant role in achieving learning objectives. Teachers must also select suitable learning media under learning objectives and student characteristics. This article aims to present the results of experiments using historical, educational games on learning outcomes. This study focuses on two learning media: educational games and animated videos. The form of research used is a quasi-experimental, with the research design used Nonequivalent Control Group Pretest Posttest Design. The research instrument used is a Learning outcome test instrument. The research procedure includes the pre-experimental testing stage, the experimental implementation stage, and the post-experiment testing stage. Eighty-two students in two classes, experimental activities were carried out. One class uses educational game media, the experimental class, and one learns using animated video media, called the control class. The experiment carries out in three stages: the preexperimental testing stage, the implementation of the experiment, and the post-experimental testing—data analysis using the U Mann Whitney test. The results showed increased student learning outcomes after using historical, educational game media, and historical animation video media. The data also show that differences in learning outcomes between students who use educational game media and animation videos in learning using historical educational games have an effect of 27.34% on improving student learning outcomes in class XI IPS SMA Negeri 3 Medan.